Penerapan BioTranspezia dengan Strategi Jigsaw Terhadap Keterampilan Komunikasi Siswa - Sulistyowati, Erna; Aryani, Ima (Bioscientist : Jurnal Ilmiah Biologi, 2025)
BioTranspezia is a multimedia that contains material about the human body's transport and exchange system accompanied by supporting images, learning videos, learning objectives, and evaluations in the form of quizzes. This multimedia is expected to be able to improve students' communication skills during learning. This research aims to improve the communication skills of grade XI students after using BioTranspezia with a jigsaw strategy. The type of research used is quasi-experimental. The research method was quantitative with the research subjects being grade XI students at SMA Batik 2 Surakarta and the research sample of students in grades XI.4 and XI.5 totaling 67 students. The research instrument using a communication skills observation sheet was made in accordance with 4 indicators, namely discussion, presentation, conveying opinions, and answering questions. The data analysis technique used is quantitative descriptive. The results of the study showed that of the total indicators in the experimental class, a percentage of 76.52% was obtained in the skilled category while the control class was 40.6% in the less skilled category. Based on the results of the study, it can be concluded that the communication skills of grade XI students at SMA Batik 2 Surakarta in the learning process can be improved through the application of BioTranspezia with a jigsaw strategy.